2020
DOI: 10.3390/molecules25092200
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Performance Challenges in Organic Photovoltaics: An Overview about Compatibilizers

Abstract: Organic Photovoltaics (OPVs) based on Bulk Heterojunction (BHJ) blends are a mature technology. Having started their intensive development two decades ago, their low cost, processability and flexibility rapidly funneled the interest of the scientific community, searching for new solutions to expand solar photovoltaics market and promote sustainable development. However, their robust implementation is hampered by some issues, concerning the choice of the donor/acceptor materials, the device thermal/photo-stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 204 publications
(238 reference statements)
0
13
0
Order By: Relevance
“…Organic electronic materials are currently drawing a broad interest due to the morphological organization and crystallinity [1][2][3] of molecular chromophores that can be synthetically engineered to tune their electronic properties. For example, in the area of organic solar cells, significant improvements in power conversion efficiencies have been recently achieved by using materials with fused aromatic units 4 At time delay T after preparation, the hybrid broadband (500 attosecond) and narrowband (3 fs) X-ray fields ε 0 and ε 1 probe the molecular dynamics via a stimulated Raman process.…”
Section: Introductionmentioning
confidence: 99%
“…Organic electronic materials are currently drawing a broad interest due to the morphological organization and crystallinity [1][2][3] of molecular chromophores that can be synthetically engineered to tune their electronic properties. For example, in the area of organic solar cells, significant improvements in power conversion efficiencies have been recently achieved by using materials with fused aromatic units 4 At time delay T after preparation, the hybrid broadband (500 attosecond) and narrowband (3 fs) X-ray fields ε 0 and ε 1 probe the molecular dynamics via a stimulated Raman process.…”
Section: Introductionmentioning
confidence: 99%
“…Although the bulk heterojunction P3HT:PCBM solar cells are presently the most widely applied devices, there are still unresolved issues about the relation between preparation method, structure of different layers, and performance of the incorporated materials [46,47]. In this paper the optical, structural, and electrical properties of environmentally prepared flexible SCs based on a P3HT:PCBM active layer were examined as a function of PET substrate behavior, post-deposition thermal annealing, application of ZnO np-based ETL, and device time degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymer additive poly (N-(4 -(9,9-dioctyl-fluoren-2-yl) phenyl)-N, N0, N0 triphenyl-l,4-phenylenediamine) (PFLAM) to the active blend of P3HT:PCBM improved the hole mobility of the device leading to an increase in the device efficiency by 34% compared to the blend without the additive material [ 100 ]. THC8, PCBTDPP, P3HT-b-PS were reported to enhance the hole mobility as well for the same active blend [ 101 , 102 ]. Studies on the effect of thermal annealing on charge carrier mobility showed that the mobility improves with annealed samples compared to non-annealed cells, although the improvement is not always in the direction of increasing temperature.…”
Section: Charge Carrier Mobilitiesmentioning
confidence: 99%